Temporary placement of a paclitaxel or rapamycin-eluting stent is effective to reduce stenting induced inflammatory reaction and scaring in benign cardia stricture models - Wang, Lin; Zhu, Yue-Qi; Cheng, Ying-Sheng; Cui, Wen-Guo; Chen, Ni-Wei (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To investigate whether temporary placement of a paclitaxel or rapamycin eluting stent is more effective to reduce stenting induced inflammatory reaction and scaring than a bared stent in benign cardia stricture models. Materials and Methods: Eighty dog models of stricture were randomly divided into a control group (CG, n=20, no stent insertion), a bare stent group (BSG, n=20), a paclitaxel eluting (Pacl-ESG, n=20) and a rapamycin eluting stent group (Rapa-ESG, n=20), with one-week stent retention. Lower-oesophageal-sphincter pressure (LOSP), 5-minute barium height (5-mBH) and cardia diameter were assessed before, immediately after the procedure, and regularly for 6 months. Five dogs in each group were euthanized for histological examination at each follow-up assessment. Results: Stent insertion was well tolerated, with similar migration rates in three groups. At 6 months, LOSP and 5-mBH improved in Pacl-ESG and Rapa-ESG compared to BSG (p<0.05), with no difference between Pacl-ESG and Rapa-ESG (p>0.05). Cardia kept more patency in the Pacl-ESG and Rapa-ESG than in BSG (p<0.05). Reduced peak inflammatory reactions and scarring occurred in the Pacl-ESG and Rapa-ESG compared to BSG (p<0.05), with a similar outcome in the Pacl-ESG and Rapa-ESG (p>0.05). Conclusion: Paclitaxel or rapamycin-eluting stents insertion led to better outcomes than bare stents in benign cardia stricture models.